Determination of Pesticide Residue Cartap Using a Sensitive Fluorescent Probe - JING, Xu; DU, Li-ming; WU, Hao; WU, Wen-ying; CHANG, Yin-xia (Journal of Integrative Agriculture, 2012)
The insecticide cartap （CP） is non-fluorescent in aqueous solutions. This property makes its determination through direct fluorescent method difficult. In acidic medium and at room temperature, palmatine （PAL） can react with cucurbit[7]uril （CB[7]） to form stable complexes, and the fluorescence intensity of the complex is greatly enhanced. Significant quenching of the fluorescence intensity of the CB[7]-PAL complex was observed with the addition of cartap. Based on the significant quenching of the supramolecular complex fluorescence intensity, a new spectrofluorimetric method with high sensitivity and selectivity was developed to determine cartap in aqueous solution. The fluorescence quenching values （AF） showed good linear relationship with cartap concentrations from 0.009 to 2.4 ~tg mL-~ with a detection limit 0.0029 ~tg mE-x. The proposed method had been successfully applied to the determination of cartap residues in grain and vegetable with recoveries of 87.4-103%. In addition, the association constants of the complexes formed between the host and the guest were determined. The competing reaction and the supramolecular interaction mechanisms between the cartap and PAL as they fight for occupancy of the CB[7] cavity were studied using spectrofluorimetry, xH NMR and molecular modeling calculations.